Skinned Deep - Gabriel, Bartalos; Butts, Bill.; Eric Bennett; John Deall; Karoline Brandt; Warwick Davis; Forrest J Ackerman; Carley, Kurt. (USA Center Ring Entertainment, 2004)
While traveling through the back woods, a family road trip turns into a horrifying nightmare. Sound familiar? It should--after all, it's the basic storyline of such seminal horror films as The Texas Chainsaw Massacre and The Hills Have Eyes. A loony matriarch and her clan of mutants hold off on doing away with pretty teenager (Tina) optimistic that she'll succumb to the charms of sensitive son Brain (he's the one with the head the size of a microwave) who desperately wants a girlfriend. Alternating between horror and humor, Skinned Deep offers up generous servings of bad acting, out-of-synch dubbing, and an outrageous storyline that is simply too unbelievable to explain (think John Waters meets John Carpenter). Still, there are some well-deserved chuckles, fun set pieces, and surprisingly creative special effects. Proudly boasts cast member Warwick Davis (Willow, Harry Potter) playing a dinner plate-wielding maniac.
Gabriel Bartalos
Language(s): English Subtitle(s): No Subtitle
Keywords: Horror; Comedy